Invasive giant reed shifts riparian habitat mosaics, with stronger effects on birds than butterflies across spatial scales - Heather L. Mackey; Lars Y. Pomara; Julie E. Coffey; Eric M. Wood (Biological Invasions, 2026)
Giant reed ( Arundo donax ) has invaded biologically diverse riparian ecosystems in warm and arid regions globally, yet its impacts on wildlife are still poorly understood. Resolving the multi-taxa, scale-explicit impacts of giant reed in the broader context of the riparian vegetation mosaics that support wildlife can help target ecological restoration efforts. We quantified effects of giant reed and other dominant riparian vegetation on bird and butterfly habitat occupancies at two spatial scales along the Rio Grande in west Texas, USA. Birds and butterflies are diverse in riparian systems and can be efficiently surveyed, making them useful indicator taxa. We surveyed 167 sites three times per year in 2016 and 2017, and used occupancy models to relate occupancy to cover proportions of dominant vegetation types derived from high-resolution aerial imagery at two scales (100 m and 500 m radii) to assess local vs. broader floodplain-scale effects. Five of 16 bird species (31%) showed negative giant reed associations at both scales, while two bird species (13%) showed positive giant reed associations and nine (56%) showed no direct effect. In contrast, no butterfly species showed direct negative associations with giant reed. However, positive associations for both butterflies and many bird species were primarily linked at both spatial scales to the vegetation types most displaced by giant reed and most likely to benefit from its control. Overall, vegetation effects were mostly at the local scale for birds, and the floodplain scale for butterflies, although negative effects of giant reed on birds persisted at the floodplain scale despite its confinement mainly to near-channel habitats. While giant reed directly impacted riparian habitat occupancy only for birds, control efforts are likely to affect both taxa positively by restoring mesic woody and herbaceous vegetation.

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Interindividual behavioural variation in response to elevated CO2 predicts mRNA transcript abundance of genes related to acid-base regulation in medaka (Oryzias latipes) - Jenna L. Fleet; Theresa E. Mackey; Jennifer D. Jeffrey; Sara V. Good; Kenneth M. Jeffries; Caleb T. Hasler (Aquatic Toxicology, 2024)

Using in-situ strain measurements to evaluate the accuracy of stress estimation procedures from fracture injection/shut-in tests - Yves Guglielmi; Mark McClure; Jeffrey Burghardt; Joseph P. Morris; Thomas Doe; Pengcheng Fu; Hunter Knox; Vince Vermeul; Tim Kneafsey; J. Ajo-Franklin; T. Baumgartner; K. Beckers; et al. (International Journal of Rock Mechanics and Mining Sciences, 2023)

The Alberta moving beyond breast cancer (AMBER) cohort study: baseline description of the full cohort - Christine M. Friedenreich; Jeff K. Vallance; Margaret L. McNeely; S. Nicole Culos-Reed; Charles E. Matthews; Gordon J. Bell; John R. Mackey; Karen A. Kopciuk; Leanne Dickau; Qinggang Wang; Diane Cook; Stephanie Wharton; et al. (Cancer Causes & Control, 2022)
Purpose The Alberta Moving Beyond B r east Cancer (AMBER) Study is an ongoing prospective cohort study investigating how direct measures of physical activity (PA), sedentary behavior (SB), and health-related fitness (HRF) are associated with survival after breast cancer. Methods Women in Alberta with newly diagnosed stage I (≥ T1c) to IIIc breast cancer were recruited between 2012 and 2019. Baseline assessments were completed within 90 days of surgery. Measurements included accelerometers to measure PA and SB; a graded treadmill test with gas exchange analysis to measure cardiorespiratory fitness (VO 2peak ); upper and lower body muscular strength and endurance; dual-X-ray absorptiometry to measure body composition; and questionnaires to measure self-reported PA and SB. Results At baseline, the 1528 participants’ mean age was 56 ± 11 years, 59% were post-menopausal, 62% had overweight/obesity, and 55% were diagnosed with stage II or III disease. Based on device measurements, study participants spent 8.9 ± 1.7 h/day sedentary, 4.4 ± 1.2 h/day in light-intensity activity, 0.9 ± 0.5 h/day in moderate-intensity activity, and 0.2 ± 0.2 h/day in vigorous-intensity activity. For those participants who reached VO 2peak , the average aerobic fitness level was 26.6 ± 6 ml/kg/min. Average body fat was 43 ± 7.1%. Conclusion We have established a unique cohort of breast cancer survivors with a wealth of data on PA, SB, and HRF obtained through both direct and self-reported measurements. Study participants are being followed for at least ten years to assess all outcomes after breast cancer. These data will inform clinical and public health guidelines on PA, SB, and HRF for improving breast cancer outcomes.

Macroalgae morpho-functional groups in Southern marine ecosystems: rocky intertidal in the Southwestern Atlantic (33°–35° S) - G. M. Vélez-Rubio; L. González-Etchebehere; F. Scarabino; R. Trinchin; G. Manta; M. Laporta; M. Zabaleta; V. Vidal; A. de Leon-Mackey; C. Kruk (Marine Biology, 2021)

Low Static Shear Modulus Along Foliation and Its Influence on the Elastic and Strength Anisotropy of Poorman Schist Rocks, Homestake Mine, South Dakota - Katherine J. Condon; Hiroki Sone; Herbert F. Wang; J. Ajo-Franklin; T. Baumgartner; K. Beckers; D. Blankenship; A. Bonneville; L. Boyd; S. Brown; J. A. Burghardt; C. Chai; et al. (Rock Mechanics and Rock Engineering, 2020)

In vivo neuroimaging and behavioral correlates in a rat model of chemotherapy-induced cognitive dysfunction - Robert L. Barry; Nellie E. Byun; M. Noor Tantawy; Chase A. Mackey; George H. Wilson; Adam J. Stark; Michael P. Flom; Laura C. Gee; C. Chad Quarles (Brain Imaging and Behavior, 2018)

Trans-ethnic fine-mapping of genetic loci for body mass index in the diverse ancestral populations of the Population Architecture using Genomics and Epidemiology (PAGE) Study reveals evidence for multiple signals at established loci - Lindsay Fernández-Rhodes; Jian Gong; Jeffrey Haessler; Nora Franceschini; Mariaelisa Graff; Katherine K. Nishimura; Yujie Wang; Heather M. Highland; Sachiko Yoneyama; William S. Bush; Robert Goodloe; Marylyn D. Ritchie; et al. (Human Genetics, 2017)

Structural dynamic analysis of the epicentral zone of the Ilin-Tas earthquake (Feb 14, 2013, Ms = 6.9) - L. P. Imaeva; B. M. Koz’min; V. S. Imaev; K. G. Mackey (Journal of Seismology, 2015)

Genome-wide association study for refractive astigmatism reveals genetic co-determination with spherical equivalent refractive error: the CREAM consortium - Qing Li; Robert Wojciechowski; Claire L. Simpson; Pirro G. Hysi; Virginie J. M. Verhoeven; Mohammad Kamran Ikram; René Höhn; Veronique Vitart; Alex W. Hewitt; Konrad Oexle; Kari-Matti Mäkelä; Stuart MacGregor; et al. (Human Genetics, 2015)

Large scale international replication and meta-analysis study confirms association of the 15q14 locus with myopia. The CREAM consortium - Virginie J. M. Verhoeven; Pirro G. Hysi; Seang-Mei Saw; Veronique Vitart; Alireza Mirshahi; Jeremy A. Guggenheim; Mary Frances Cotch; Kenji Yamashiro; Paul N. Baird; David A. Mackey; Robert Wojciechowski; M. Kamran Ikram; et al. (Human Genetics, 2012)

Major Conservation Policy Issues for Biodiversity in Oceania - R. T. KINGSFORD; J. E. M. WATSON; C. J. LUNDQUIST; O. VENTER; L. HUGHES; E. L. JOHNSTON; J. ATHERTON; M. GAWEL; D. A. KEITH; B. G. MACKEY; C. MORLEY; H. P. POSSINGHAM; et al. (Conservation Biology, 2009)
Oceania is a diverse region encompassing Australia, Melanesia, Micronesia, New Zealand, and Polynesia, and it contains six of the world's 39 hotspots of diversity. It has a poor record for extinctions, particularly for birds on islands and mammals. Major causes include habitat loss and degradation, invasive species, and overexploitation. We identified six major threatening processes (habitat loss and degradation, invasive species, climate change, overexploitation, pollution, and disease) based on a comprehensive review of the literature and for each developed a set of conservation policies. Many policies reflect the urgent need to deal with the effects of burgeoning human populations (expected to increase significantly in the region) on biodiversity. There is considerable difference in resources for conservation, including people and available scientific information, which are heavily biased toward more developed countries in Oceania. Most scientific publications analyzed for four threats (habitat loss, invasive species, overexploitation, and pollution) are from developed countries: 88.6% of Web of Science publications were from Australia (53.7%), New Zealand (24.3%), and Hawaiian Islands (10.5%). Many island states have limited resources or expertise. Even countries that do (e.g., Australia, New Zealand) have ongoing and emerging significant challenges, particularly with the interactive effects of climate change. Oceania will require the implementation of effective policies for conservation if the region's poor record on extinctions is not to continue .

ELEMENTS IN LIVER TISSUES OF BOWHEAD WHALES ( BALAENA MYSTICETUS ) - Cheryl A. Krone; Paul A. Robisch; Karen L. Tilbury; John E. Stein; Elizabeth A. Mackey; Paul R. Becker; Todd M. O'hara; L. Michael Philo (Marine Mammal Science, 1999)
A bstract Livers from 20 bowhead whales taken in subsistence hunts at Barrow, Alaska, were analyzed for essential and non‐essential elements. Concentrations of essential elements were similar to those found in other cetaceans. Non‐essential element concentrations were generally comparable to other baleen whales and very low compared to most odontocetes. One deviation from this pattern was a relatively high level of hepatic cadmium that may be related to specific dietary factors of this krill‐dependent species. No sex‐related differences were found in element concentrations. Hepatic cadmium and mercury increased with animal length, and significant positive interelement correlations were found between copper/zinc and mercury/selenium. We found a mercury‐toselenium ratio much lower (1:40) than the frequently reported ratio of one to one. The data suggest that further studies of the postulated mercurydetoxifying role of selenium are warranted.

Erratum - M. L. Magoon; R. W. Hougas; D. C. Cooper; J. M. Hartman; Andrea Mackey; Joy Stockman; Ora Smith; J. W. Scanneil (American Journal of Potato Research, 1958)